Pengaruh Pemberian Susu Kedelai terhadap Gejala Hot Flush pada Wanita Perimenopause - Gita Taris Alvionita; Indah Kurniawati; Renita Rizkya Danti (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2025)
Women entering the perimenopausal and menopausal phases usually experience hot flushes or sudden sensations of heat. The WHO reports the prevalence of hot flushes is estimated at 75% to 85%. One intervention for perimenopausal women with hot flushes is providing foods or drinks rich in phytoestrogens, such as soy milk, which contains isoflavones that can reduce the intensity of hot flushes. This study aimed to determine the effect of soy milk consumption on hot flush symptoms in perimenopausal women in the Mojopanggung Community Health Centre working area in 2025. The study was conducted over 14 days using a non-equivalent pre-posttest with control group design. The study population consisted of 60 perimenopausal women. The sampling technique used was consecutive sampling. The bivariate test used was the Mann–Whitney test. Instruments included observation sheets and a hot flush diary measurement tool. Results in the intervention group showed moderate and severe hot flushes before the intervention and mild and moderate categories after the intervention; the control group remained in the moderate and severe categories. The Mann–Whitney test yielded a p-value < 0.001, indicating that soy milk had an effect on hot flush symptoms in the intervention group. This study is expected to improve the standard of care for perimenopausal women experiencing hot flushes in the Mojopanggung Community Health Centre working area. It is hoped that midwives can help reduce hot flushes by providing complementary soy milk intake.